Efficient and Secure Authentication Protocol for VANET - Hui Liu; Hui Li; Zhanxin Ma (2010 International Conference on Computational Intelligence and Security, 2010)
VANET is very important for improving traffic safety and efficiency. So the messages in VANET must be trustworthy and disseminated very fast. In this paper, an efficient and secure scheme is proposed for VANET messages authentication, group signature is used for the messages from private vehicles and identity-based signature for public vehicles and RSU, further more, it employs batch message-processing techniques to accelerate the verification. Quantitative comparison determination is explored for handling conflicting information. Extensive simulation is conducted to confirm the efficiency of the scheme in various application scenarios. The results show that the scheme is better than other similar programs.